If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 45(15 + m) = 1935 (15 * 45 + m * 45) = 1935 (675 + 45m) = 1935 Solving 675 + 45m = 1935 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-675' to each side of the equation. 675 + -675 + 45m = 1935 + -675 Combine like terms: 675 + -675 = 0 0 + 45m = 1935 + -675 45m = 1935 + -675 Combine like terms: 1935 + -675 = 1260 45m = 1260 Divide each side by '45'. m = 28 Simplifying m = 28
| 1/2a+1=9/8 | | -2/3-2b=-68/3 | | 9+4/5m=93/5 | | 6-3/5t=18/5 | | -8+7f=-22 | | -x^2+13x-40=0 | | -1/6+3/7x=47/42 | | 8-5t=23 | | -7k-10=-27/2 | | 4/7m+9=99/7 | | 3-3n=33 | | 1-2k=-5/11 | | 8y-0.1=9y | | (7w+2)(7w+2)= | | 6/7k-1/2=5/14 | | 3/7k-5=-257/49 | | 3/7n+2=47/7 | | -6x-10=-55/4 | | 3t+4=28 | | 4+5n=21/4 | | -3/4b+3/8=69/8 | | -8-m=-8 | | 8+1/3k=239/30 | | b+6=-5 | | 2m-8=-14 | | b+7/8=79/8 | | -14=3-C+(9+5C) | | 10x^2+3x=11x | | 5y+10xy=20 | | 1-7b=-11/3 | | 5+4/7m=-13/7 | | 4w-1=7 |